500 HEMODYNAMIC FORCES AS PREDICTORS OF CARDIAC REMODELING AND OUTCOME IN PATIENTS WTH HEART FAILURE WITH REDUCED EJECTION FRACTION TREATED WITH SACUBITRIL/VALSARTAN. (15th December 2022) - Castiglione, Vincenzo; Fabiani, Iacopo; Pugliese, Nicola Riccardo; Pedrizzetti, Gianni; Tonti, Giovanni; Chubuchny, Vladislav; Taddei, Claudia; Gimelli, Alessia; Del Punta, Lavinia; Balletti, Alessio; Masi, Stefano; Cameli, Matteo; et al.
Abstract: Aims: To evaluate the predictive value of echo-derived hemodynamic forces (HDF) compared to other echocardiographic, biohumoral and cardiopulmonary parameters on: a) angiotensin receptor-neprilysin inhibition (ARNI) response to 6-months treatment; b) cardiovascular events at follow-up. Methods: Eighty-nine consecutive patients with heart failure with reduced ejection fraction (HFrEF) performed clinical, laboratory, ultrasound, and cardiopulmonary exercise testing. Patients experiencing no adverse events and showing ≥50% reduction in plasma N-terminal pro-B-type natriuretic peptide (NT-proBNP) and/or ≥10% increase in left ventricle ejection fraction over 6 months were considered responders to ARNI. We conducted a clinical follow-up for the composite endpoint of HF-related hospitalization, new-onset atrial fibrillation and cardiovascular death. Results: Out of 89 patients, 45 (51%) were ARNI-responders. Among several variables evaluated at baseline, only the whole cardiac cycle left ventricle strength (wLVS) calculated from HDF was found to be higher in responders (4.4±1.3 vs 3.6±1.2; p=0.01) and the only independent predictor of ARNI-response at multivariate logistic regression analysis (odds ratio 1.36; 95% confidence interval 1.10–1.67; p=0.004), with good accuracy at receiver operating characteristic (ROC) analysis (optimal cut-off ≥3.7%; area under the curve [AUC]=0.736, 0.607–0.840; p<0.0001). During a median follow-up of 33 months (interquartile range 23-41), 6-month wLVS increase (ΔwLVS) showed a high discrimination ability at time-dependent ROC analysis (optimal cut-off ≥0.5%; AUC=0.811, 0.69–0.90; p<0.0001), stratified prognosis (log-rank p<0.0001) and remained an independent prognostic predictor for the composite endpoint (hazard ratio 0.76, 0.61–0.95; p<0.01), after adjusting for all clinical, functional and conventional echocardiographic parameters (Figure). Conclusions: HDF analysis helps in predicting ARNI-response and optimizing follow-up and medical/device decision-making in patients with HFrEF.